Towards a Definition of Distinction in Professionalism. Issue 2 (14th March 2020) - Ali, Anthony; Anakin, Megan; Tweed, Mike J.; Wilkinson, Tim J.
Abstract: Phenomenon: Professionalism can be characterized by a particular set of attributes that clinicians demonstrate in practice. Although much has been described on those attributes that define acceptable professionalism, the characteristics that define distinction in professionalism have not yet been well defined. Approach: In this exploratory project, qualitative methods were used to triangulate three sources of data collected from three campuses of one medical school: student assessment summaries, teacher interviews, and an institutional policy. Findings: One hundred-thirty student assessment summaries, eight teacher interviews, and one institutional policy were analyzed. Three characteristics emerged that define distinction in professionalism: improvement of oneself, helping others learn, and teamwork. These characteristics are in addition to students demonstrating a clear minimum standard in all other aspects of professionalism. Insights: Findings from this project offer a first step toward a definition of distinction in professionalism for assessing student performance. The characteristics can be demonstrated by students to varying degrees of proficiency and are potentially achievable by all students. Finally, the characteristics would be required in addition to demonstrating a clear minimum standard of performance in all other aspects of professionalism and cannot be inferred by the absence of negative or unprofessional behaviors. Recognizing that conceptions of professionalism have contextual and cultural influences, the characteristics of distinction identified by this project expand the language available for teachers and learners to discuss professionalism. Teachers may use these characteristics to help inform their teaching, learning, and feedback practices. Students will gain clarity about the expectations regarding their professional behavior.